Effect of solvent on percentages yields of condensed tannin in different types of tea (Camellia Sinensis) / Noor Fadlyana Mail - Mail, Noor Fadlyana (Faculty of Applied Sciences, 2009)
Plant condensed tannins (proanthocyanidins, PAs) have both positive and negative effects on feed digestibility and animal performance, depending both on quality and biological activity of the tannins that are present. In this project, analyses of condensed tannins (PAs) are examined. Our focus is on the analytical method used to evaluate tannins. The section on methods is subdivided into a discussion of methods to determine the amount of condensed tannins or total phenolics in a sample and a section on extracted condensed tannins by using different solvents. The effects of different extracting solvents, used in Butanol-hydrochloric acid method, on the total condensed tannins contents of green tea, black tea and oolong tea were studied. Water and organic solvents, used in mixtures: acetone/water/ (80/20) and methanol/water (80/20), significantly affected total condensed tannins content. The results showed that solvents with different polarities had significant effects on total of condensed tannins. The condensed tannins of samples were extracted using methanol and acetone at same concentrations with water. Among solvents tested, 80% acetone, containing 20% water, extracted a maximum amount of condensed tannins from green tea, black tea and oolong tea. Condensed tannins extracted were assayed using a 2% ferric ammonium sulphate solution containing 2M HC1 (v/v). The green tea contains the higher amount of condensed tannin in both solvent extraction following by oolong tea and black tea.